ORAL SQUAMOUS PAPILLOMA ASSOCIATED WITH HPV: DIFFERENTIAL DIAGNOSIS WITH OTHER VERRUCOUS LESIONS (International Seven Journal of Health Research, 2025)
Oral squamous papilloma is a benign epithelial lesion primarily associated with human papillomavirus (HPV) infection, clinically characterized by verrucous or papillomatous projections affecting the tongue, palate, and buccal mucosa. Despite its non-neoplastic nature, it presents clinical similarities with other verrucous lesions of the oral cavity, such as verruca vulgaris, condyloma acuminata, focal epithelial hyperplasia, and verrucous carcinoma, making differential diagnosis a clinical and histopathological challenge. Recent studies indicate a higher prevalence of low-risk genotypes, such as HPV 6 and 11, in oral squamous papilloma, although high-risk types, such as HPV 16 and 18, may be associated with the potential for malignant transformation. The literature highlights the importance of detailed histopathological analysis, complemented by immunohistochemical tests and polymerase chain reaction (PCR), as fundamental tools for accurate diagnostic differentiation. Correct differentiation of oral squamous papilloma from other verrucous lesions enables appropriate therapeutic approaches, prevents erroneous approaches, and contributes to targeted clinical monitoring, with a direct impact on dental practice and the prevention of complications.